The Impact of COVID-19 on the Work System's Influence on Care Processes and Ambulation Outcomes - Jones-Hooker, Christa (East Carolina University, 2022)
Ambulation is one of the most frequently reported missed nursing care activities for hospitalized patients. The COVID-19 pandemic forced hospitals to make systems changes to minimize transmission of the disease and compromised the ability of hospitals to promote ambulation. The impact of systems changes on ambulation care processes was unknown, creating a gap in the literature. This study aimed to address this gap in knowledge by exploring hospital changes influencing ambulation from a systems perspective A single case study research design was used to explore the impact of COVID-19 on the work system’s influence on care processes and ambulation outcomes. A systems perspective of ambulation was achieved by using the Systems Engineering Initiative for Patient Safety (SEIPS) model of work system and patient safety to guide the study. A large academic medical center located in the southeast region of the United States (U.S.) was selected as a critical case for this single case study research design. Purposeful sampling was used to select 12 leaders representing the following disciplines: nursing, physical therapy, occupational therapy, respiratory therapy, and epidemiology/infection prevention. The primary source of data was interviews, which were triangulated with documents and direct observations. Data analysis included first and second cycle coding for labels, sorting for patterns, identifying outliers, and reflecting. Patterns were identified using Microsoft Word documents, drawings, matrices, and models/diagrams. Analysis revealed the patterns of influence of COVID-19 on ambulation care processes. The findings were categorized as the external environment, work system, and ambulation care processes. Findings showed COVID-19 was a significant source of stress on the work system. This additional stress from the pandemic forced changes in the daily operations of the work system. Although changes were necessary, they were barriers to ambulation (staff shortages, visitor restrictions, and mask supply shortages) which disrupted usual care processes. When visitor restrictions removed family members from the work system, the value of informal ambulation care processes provided by family members was revealed. This study is significant in providing new knowledge related to informal ambulation care processes and broadening the definition of external environment to include pandemics. Understanding how the external environment and work system influence informal care processes may help facilitate the design of system-level ambulation policies and programs. Future studies should further examine the value of informal care processes occurring in the hospital setting.
Keywords: Ambulation; hospital; inpatient; COVID-19; missed care; SEIPS model; informal care